2020
DOI: 10.1007/s00167-020-06219-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of tranexamic acid (TXA) to intra-articular tissue in orthopaedic surgery: a scoping review

Abstract: Purpose Intra-articular administration of tranexamic acid (TXA) in orthopaedic arthroplasty and arthroscopic procedures has become increasingly common over the past decade. However, several recent reports have shown that TXA has the potential to be cytotoxic to cartilage, tendon and synovium. Our aim was to review the literature for evidence of toxic efects from TXA exposure to intra-articular tissue. Methods A scoping review methodology was used to search for studies assessing the toxic efects of TXA exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…There is a lack of understanding about how rapidly TXA diffuses out of the joint space following intra-articular administration or to what degree it is diluted by bleeding or synovial fluid. In addition, the dynamic environment of the joint space and the presence of other cells types (inflammatory cells and platelets) could have a role in the absorbance of TXA into surrounding tissues [ 6 ]. During arthroplasty, TXA has been shown to diffuse rapidly into synovial fluid after IV administration, equal to serum concentrations, and the half-life in synovial fluid is 3 h [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a lack of understanding about how rapidly TXA diffuses out of the joint space following intra-articular administration or to what degree it is diluted by bleeding or synovial fluid. In addition, the dynamic environment of the joint space and the presence of other cells types (inflammatory cells and platelets) could have a role in the absorbance of TXA into surrounding tissues [ 6 ]. During arthroplasty, TXA has been shown to diffuse rapidly into synovial fluid after IV administration, equal to serum concentrations, and the half-life in synovial fluid is 3 h [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…TXA (Trans-4-amino-methylcyclohexane-1-carboxylic acid) was obtained from Apollo Scientific (Stockport, UK). The cells in each experiment were exposed to TXA in ranges of concentrations to mimic the range that could be expected following intra-articular administration (0, 10, 20, 35, 50 or 100 mg/mL), with specific graduations of TXA chosen to better define the toxic threshold previously predicted to be 20 mg/ml [ 4 , 6 , 18 , 20 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IA administration of TXA is increasingly cited as a preferred route, producing comparable postoperative systemic coagulation and fibrinolytic profiles to systemic administration [ 37 ]. However, there is controversial evidence of TXA chondrotoxicity following topical administration [ 17 , 18 , 36 , 38 ]. Given the ongoing controversies, we believe current guidelines should address the indiscriminate use of TXA and recommend against its widespread use in major surgery, like TKA, without first demonstrating the presence of hyperfibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular TXA has been used in some RCTs, but there remains a concern due to a potential cytotoxic effect of TXA on cartilage, tendons, and synovial tissue. A recent scoping review in-cluded 15 laboratory studies, as no clinical study reporting a toxic effect was found [47]. They conclude that the current evidence suggests a dose-dependent toxic effect on cartilage, tendons, and synovial tissue, but that concentrations of 20 mg/ml TXA or less are expected to be safe.…”
Section: Arthroscopymentioning
confidence: 99%